A Mobile Phone in One Hand and Erskine May in the Other: The European Research Group's Parliamentary Revolution. Issue 3 (2nd March 2021) - Murray, C R G; Armstrong, Megan A
Abstract: It has become axiomatic that backbench Members of Parliament (MPs) at Westminster have limited the capacity for independent action under the burdens of constituency business and whipped votes. Even the limited avenues available for such MPs to shine, such as select committees, are often illusory because parliamentarians have little time to prepare the materials or brief themselves on any but the highest profile witnesses. The political parties have benefitted from this state of affairs; docile MPs make for reliable votes. The rise of the European Research Group (ERG) as a parliamentary force disrupts this narrative. Galvanised by single-issue opposition to the UK's involvement in 'Europe', encompassing both the European Union (EU) and the European Convention on Human Rights (ECHR), the Group successfully exploited the balance of power in the Commons during the 2017–2019 Parliamentary Session. This article analyses the methods by which the Group's members magnified their influence over Brexit debates.